Lithofacies, mineralogy, and pore types in Paleozoic gas shales from Western Peninsular Malaysia - Ibad, S.M. (Elsevier B.V., 2022)
An experimental study including Fourier Transform Infrared (FTIR), thin section petrography, scanning electron microscope (SEM) imaging, and low-pressure nitrogen adsorption analysis has been conducted to assess the mineralogy, lithofacies, pore types, and pore properties of the potential Paleozoic gas shales from Western Peninsula (WP) Malaysia. In WP Malaysia, shale samples from seven Paleozoic Formations were investigated and classified into four age categories. FTIR analysis documented the presence of aromatic out of plane and in plane bending, aliphatic CH bending, OH functional group, and presence of quartz, carbonates, kaolinite, and illite minerals. Four lithofacies identified from the petrographic analysis of the Paleozoic shale include silica-rich argillaceous mudstone (SAM), clay-rich siliceous mudstone (CSM), silica dominated lithofacies mudstone (SD), and mixed carbonate mudstone (MCM). In comparison, the mineral content and lithofacies found in Paleozoic shales are close to the Niutitang, Longmaxi, Marcellus, and Eagle Ford shales. Furthermore, with high organic matter content, laminated fabric, and with more brittle mineralogy, SD lithofacies would be a highly promising type of lithofacies in WP Malaysia. FESEM studies show that organic matter pores, interparticle pores, and intraparticle pores are the main pore types. Pore sizes analyze through N2 adsorption reveal radii of lesser than 25 nm contribute mainly to porosity and total pore volume. Micropore volume of the WP Malaysia shale was found to be greatly similar to hot shales from USA and China, while surface area values of only older Paleozoic shales, i.e., S-D and Devonian, are close to USA shales. Â© 2022 Elsevier B.V.